Aspectos clínicos e epidemiológicos de pacientes portadores de cardiopatia chagásica crônica com cardiodesfibrilador implantável - Pereira, Francisca Tatiana Moreira (2013)
Chagas disease is one of the major social-medical problems of Brazil. Sudden death is one of the clinical phenomena characteristic of the Chagas disease since their initial descriptions. More than 50% of mortality in patients with Chagas disease are attributable to sudden cardiac death. The Implantable Cardioverter-defibrillator (ICD) has become the main therapeutic strategy for prevention of sudden death. However, the efficacy and safety of treating Chagas patients with CDI was assessed in a few observational studies. The aim of this paper was to evaluate the clinical, epidemiological and outcome of patients with chronic Chagas heart disease and implantable cardioverter-defibrillator in the state of Ceará. This was retrospective, descriptive and analytical study. The population consisted of chagasic patients with ICD for primary or secondary prevention of sudden death, enrolled at a sole university hospital. For comparative analysis, we included patients with ischemic cardiomyopathy and ICD for primary or secondary prevention of sudden death. The outcomes analyzed were: appropriate therapy (shock therapy and appropriate antitachycardia), appropriate shock, mortality and event-free survival (appropriate shock, appropriate therapy or death). Results: 146 patients were evaluated, 63 (42.5%) chagasic patients with median follow-up time of 27 months (Q1 = 9.0 and Q3 = 47) and 83 (57.5%) with a median of ischemic follow-up time of 35 months (Q1 = Q3 = 22 and 59). The annual mortality rate, the incidence of sudden death, the incidence of arrhythmic storm and the incidence of inappropriate shock were similar in both groups. The ischemic patients were on average 10 years older than the Chagas patients (p <0.001). Observed appropriate therapy triggered by CDI in 27 (42.9%) chagasic patients and 14 (16.9%) ischemic (p = 0.001). Appropriate shock was observed in 23 (36.5%) chagasic patients and 14 (16.9%) ischemic. Chagas heart disease increased by 2.07 times (95% CI: 1.02 to 4.17) the risk of the patient receiving appropriate therapy. The functional class (I to IV), ejection fraction (normal or mild dysfunction to severe) and type of prevention were not predictors of shock or appropriate therapy in patients with Chagas heart disease. There was no significant difference in survival time between patients with Chagas disease and the ischemic ones. The event-free survival (shock, appropriate therapy and death) was similar in both groups (Chagas disease and ischemic). There was no sudden death during follow-up of patients with Chagas disease. The low educational level (HR = 4.6 95% CI 1.6 to 13.3) and the ejection fraction of the left ventricle less than 30% (HR = 6.3 95% CI 1.2 to 31.7) were associated significantly with the outcome of death. Conclusions: The higher frequency of appropriate shock therapy in chronic Chagas disease is consistent with the presence of an arrhythmogenic substrate. Despite this higher frequency, there was no sudden death following, which suggests the effectiveness of ICD in patients with Chagas disease. The lack of difference in the rate of appropriate therapy or appropriate shock among chagasic patients with and without ventricular dysfunction suggests that LVEF should not be used as a preponderant and decisive criterion of the defibrillator indication in these patients.